The impact of the principle of reasonable division on achieving the justice of the division of constituencies: Comparative Study - يونس مها بهجت; امين اقبال عبد الله (Journal of Legal Sciences, 2021)
The reasonable division of the constituencies will lead to the stability of the political system. As long as the citizen will vote and will have an impact on the electoral process, his vote should be equal to the votes of the voters in the other constituencies. And the basic guarantee of the application of justice in all the joints of the process of division by virtue of the generality and the ability to develop and appropriate for any time and place to be applied in it, and the principle of division is a reasonable general principle with a broad concept under which many applications that differ from d According to him, another philosophy adopted by that State and the nature of the legal organization, and the degree of political awareness of its citizens.